CONSTRUCT ANALYSIS OF STEAM MITIGATION ACTIVITIES TO FOSTER CREATIVITY - Siska Pramasdyahsari, Agnita; Puspita Arum, Julia; Esti Utami, Rizky; Prasad Pant, Binod (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
The research’s aim to design class VII mathematics activity designs and determine the validity of STEAM mitigation-based activity designs to improve creative thinking skills. The method used in this research was research and development (R&D). The design development process in this activity adopts a 4D development model which consists of 4 stages, namely Define, Design, Develop, and Disseminate. The result is an activity design that can be used as a guide for teachers and students. This design then went through validation stages, namely design validation and practicality test questionnaire validation involving 5 validators, namely, 2 mathematics education lecturers, 1 SEAQIM person, and 2 mathematics teachers. The novelty of this study is the application of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) development model which focuses on activity-based mitigation in mathematics learning to improve students' creative thinking abilities. This research produces activity designs that are validated by experts in the field of mathematics education and teaching practice, ensuring that the designs are not only theoretical but also practical and ready for use in the classroom. This approach offers a new way to make mathematics learning more relevant and interesting for students, while emphasizing the importance of creative thinking in real contexts.